Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content:1. Adaptive of the bee algorithm with an overall pattern extractor to improve the fingerprint matching process Ebrahim Omar Al Shami, Marah Bassem Ali2. War disasters and their effects on urban structure, historic buildings, local people and architectural heritageEng. Hussain Saleh Mohammed Al-Kawafi3. Visual Pollution of Commercial Street Sidewalks: A Case Study of Design Standards in Al-Hilla City, IraqAthraa Hamza Hussein, Mohammad Ali Al-Anbari4. A Review on the Economic Assessment of Integrating Macro-Encapsulated Phase Change Material in Building EnvelopesAmal Ahmed, Germin Elgohary, Ashraf Nessim5. A Systematic Literature Review of Recent Blockchain PlatformsMalak Sulaiman Alrumaih, Mohammad Mahdi Hassan  Muhammad Ali Martuza,  Suliman A. Alsuhibany6. Optimization of Double-Skin Façades for Heating and Cooling in High-Rise Buildings: A Case Study in Kuwait CityEng. Fawaz Khaled Ghaith, Eng. Mohammad Hamad Buhamad
Keywords: Journal of Engineering Sciences and Information Technology